Long non‐coding RNA TUG1 participates in LPS‐induced periodontitis by regulating miR‐498/RORA pathway. (3rd September 2020) - Huang, Nannan; Li, Chanxiu; Sun, Wenjuan; Wu, Jian; Xiao, Feng
Abstract: Aim: This study was aimed to investigate the role of TUG1 in LPS‐stimulated hPDLCs and to evaluate the potential functions of TUG1 in the pathogenesis of periodontitis. Methods: LPS‐stimulated hPDLCs were established as the cell model. CCK‐8 assay was performed to assess cell proliferation ability. Flow cytometry was performed to detect cell cycle distribution, and quantitative RT‐PCR and Western blotting were conducted to measure gene expressions. ELISA kits were used to evaluate the production of inflammatory cytokines. The putative binding site between TUG1 and miR‐498 was verified using luciferase reporter and RNA immunoprecipitation assays. Results: TUG1 was downregulated upon LPS stimulation in hPDLCs. TUG1 overexpression promoted cell proliferation through regulating the cell cycle distribution, along with the decreased expression of p21 and increased expression of CDK2 and cyclin D1. Besides, TUG1 overexpression decreased the production of inflammatory cytokines. The effects were opposite upon TUG1 knockdown. TUG1 negatively regulated its target miR‐498, and influenced the expression of RORA, the direct target of miR‐498. Simultaneous TUG1 overexpression and miR‐498 reversed the effect of TUG1 overexpression alone on alleviating LPS‐induced cell injury and inhibition of Wnt/β‐catenin signaling, which was further changeover after co‐overexpression with RORA. Conclusion: Therefore, TUG1 could protect against periodontitis via regulating miR‐498/RORA mediated Wnt/β‐catenin signaling.